Comparison of two video prompting interventions to teach daily living skills to adolescents with autism. (11th October 2022) - Wertalik, Jennifer L.; Kubina, Richard M.
Abstract: The present study used an adapted alternating treatment design to evaluate and compare the effects of video prompting (VP) and video prompting plus frequency building (VP + FB) to teach daily living skills to three adolescents with autism spectrum disorder. Results demonstrated all three students made substantial improvements over their baseline performance using VP and VP + FB. Furthermore, a strong intervention effect emerged for VP and VP + FB conditions when compared to the control task. However, in terms of one intervention proving superior to the other (e.g., VP to VP + FB), the data offer a mixed interpretation with VP + FB affecting changes better for two of the three students. The FB component in the VP + FB produced strong, consistent gains for all students in terms of retention.